The role of surfactant in, and a comparison of, the permeability of porcine and human epithelia to various chemical compounds - Viljoen, Ianda (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScMedSc (Pharmacology))--University of Stellenbosch, 2005.